Importance of gender in students demand for higher education in tourism: The case study of a tourism and hospitality higher education institution - Salgado, Manuel (2014)
The importance of the scientific area of tourism, particularly in higher education, requires an analysis and interpretation of its evolution in Portugal. Assuming the widespread recognition of tourism and leisure transversal influence in the contemporary society, one considers the need for rigorous studies on the implications of gender issues in knowledge production in higher education institutions (HEI). Therefore, this study intends to understand the trends in students’ demand for a degree in the tourism field and the importance of gender in higher education, and also their implication in the tourism sector labour market. This study is aimed mainly at interpreting the concern to understand the need and importance of studies on gender issues in tourism higher education, from different perspectives. To determine that the image of an HEI and the students’ demand for this field of study may rely on a policy and strategy that include these relevant gender issues, both in an educational and in an employment perspective, which is also a purpose of this study. In the tourism sector, according to Costa, Carvalho and Breda (2011, p. 39), the Portuguese reality is vertically segregated and, despite being a feminised sector, men occupy most top-level positions. Moreover, tourism workers, particularly female workers, are in general subject to poorer conditions of employment, such as low-pay, long working hours and more precarious contracts. The data [collected by these authors] hint at a very wide gender pay gap in the tourism industry. Costa, Carvalho, Caçador and Breda (2012, p. 70) also analysed the higher education and the labour market in the tourism sector and concluded that although women prevail among tourism graduates in Portugal, men earn higher salaries and fill most top-level positions in the tourism sector. [Their] study diagnose[d] disparities between male and female tourism graduates in the following domains: areas of activity, positions, and salary.